USE OF CLAYS AS ADSORBENTS FOR BLEACHING USED MOTOR OILS (Web of Technology: Multidimensional Research Journal, 2025)
This article examines current environmental issues related to the disposal and regeneration of used motor oils. Modern motor oils are alloyed lubricants, typically containing several alloying additives that significantly improve the performance properties of the resulting motor oils. During use, motor oils undergo degradation processes as a result of thermochemical reactions, which lead to oil aging and a decrease in its quality. The processes occurring in oils can be divided into thermal transformations, oxidation, and sedimentation.Изменения состава масла обусловлены окислением, термическими превращениями и потерей коллоидной стабильности. As a result, used oils contain numerous undesirable impurities, including asphaltene-resinous and organometallic components. Therefore, when regenerating used motor oils, it is necessary to bleach the used oils using appropriate adsorbents The paper presents the results of scientific research on the feasibility of using new adsorbents obtained from local mineral resources in the bleaching and purification of used motor oils. The study examined the physicochemical and adsorption properties of natural mineral deposits. Turkestan Region, and conducted scientific experiments on the regeneration of waste oils using natural minerals. The results demonstrated the potential and economic feasibility of using clays from Turkestan Region deposits for bleaching waste motor oils. Based on a study of the chemical composition of local clays, the authors showed that the high content of aluminosilicates – silicon oxides (up to 58.4%) and aluminum (up to 16.03%) – is an indicator of their high adsorption activity. It has been established that local clays are valuable raw materials for use after appropriate processing for adsorption purification of mineral oil and can be an alternative to imported bleaching clays.